2023
DOI: 10.1177/15248380231162971
|View full text |Cite
|
Sign up to set email alerts
|

Influence of Cultural Norms on Formal Service Engagement Among Survivors of Intimate Partner Violence: A Qualitative Meta-synthesis

Abstract: For victim-survivors of intimate partner violence (IPV), receiving help from formal services such as specialist family violence, health, or criminal justice services can be critical for their safety and well-being. Previous research has found cross-cultural differences in the rates of help-seeking behavior, with women from non-Anglo-Saxon communities less likely to seek formal help than Anglo-Saxon populations. This qualitative meta-synthesis has integrated qualitative evidence to examine the relationship betw… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
8
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 12 publications
(8 citation statements)
references
References 72 publications
0
8
0
Order By: Relevance
“…These cultural norms are fundamental in guiding service engagement and continuation in response to IPV experiences (Green et al, 2024). Research has identified specific cultural beliefs that may influence service engagement, including fatalism and traditional gender roles (Green et al, 2024). Studies also indicate that IPV stigma, influenced by cultural messages, may impact access to services (e.g., Overstreet & Quinn, 2013).…”
Section: Cultural Environment Influences On Services Engagementmentioning
confidence: 99%
See 3 more Smart Citations
“…These cultural norms are fundamental in guiding service engagement and continuation in response to IPV experiences (Green et al, 2024). Research has identified specific cultural beliefs that may influence service engagement, including fatalism and traditional gender roles (Green et al, 2024). Studies also indicate that IPV stigma, influenced by cultural messages, may impact access to services (e.g., Overstreet & Quinn, 2013).…”
Section: Cultural Environment Influences On Services Engagementmentioning
confidence: 99%
“…Unfortunately, few survivors seek formal help (i.e., help from an institution or organization), and many discontinue services prematurely (i.e., they disengage from services before they can fully benefit or before reaching the recommended duration; Craven et al, 2023). Many factors, including stigma, cultural beliefs, and the abusive experiences themselves, play a crucial role in service engagement (Green et al, 2024; Overstreet & Quinn, 2013). While vast knowledge exists on the factors preventing help-seeking behaviors (Robinson et al, 2021), less is known about the characteristics of women who access formal support.…”
Section: Cultural Environment Influences On Services Engagementmentioning
confidence: 99%
See 2 more Smart Citations
“…Overall, literature reflects and reinforces the cultural norms and power structures associated with hegemonic masculinities, shaping societal perceptions and behaviours. Liu et al (2022) or Green, Satyen, & Toumbourou (2024) state that cultural norms play a significant role in literature, influencing translation practices and the portrayal of characters. Al-Fouzan (2019) adds that translators face challenges when dealing with culture-specific references, often resorting to adaptation by deletion, replacement, or addition to bridge cultural gaps.…”
Section: Hegemonic Masculinities In Literaturementioning
confidence: 99%